Ocular Abnormalities in Parkinsonism: A Clinical Study - Jasmine Kalyani; S. Saravanan; Jason Ambrose; Ravi, Shankaranarayanan (Medical Research and Its Applications Vol. 8, 2024)
This clinical study has been carried out with the purpose of providing an overview of eye movement abnormalities in Parkinson’s disease. The eye is a biological camera that has been endowed with us, and while tracking ocular movement is a simple activity, it offers valuable insights into the diagnosis of Parkinson’s disease. While many of the abnormalities are generic, some are quite specific, such as progressive supranuclear palsy or oculogyric crisis in post-encephalitic Parkinson’s disease. The eye symptoms of parkinsonism are vague. Retina contains dopamine, hence ocular symptoms like astenopia are common in PD. In the neurology outpatient department, a cohort of 100 patients diagnosed with Parkinson’s disease and Parkinson’s plus syndromes were meticulously examined. Demographic details, detained history, ocular signs and symptoms, ocular deviation, visual acuity, diagnosis, and management aspects are extracted from the medical records. Visual acuity by Snellen values. Ocular deviations were measured by prism cover test and ocular motility was carried out to evaluate the gaze limitation. A diagnosis of CI was made if the near point of convergence (NPC) value was larger than 10cm. Saccade and pursuit scores evaluated using the Northeastern State College of Optometry method were used to determine if they had lower than age-expected norms. Color vision was assessed using Ishihara pseudo isochromatic plates. Reading speed was measured in words per minute (WPM) based on reading a simple paragraph in an English magazine for a minute. The developmental eye movement (DEM) rate was calculated based on the time taken for the vertical and horizontal tasks on the DEM test. The protocol of eye movement examination was followed. The study highlights the significant burden of ophthalmologic symptoms in PD and emphasizes the importance of addressing these symptoms in the management of the disease. The Parkinsonian group of illnesses is distinct in that most of the time, eye movements are disturbed, providing us with important diagnostic information. The most commonly impacted are smooth pursuit fixations and saccades.